Identifying a Novel Bile Salt Hydrolase from the Keystone Gut Bacterium Christensenella minuta - Guillaume Déjean; Héloïse Tudela; Lisa Bruno; Déborah Kissi; Georges Rawadi; Sandrine P. Claus (Microorganisms, 2021)
Christensenella minuta are human gut dwelling bacteria that have been proposed as key members of the gut microbiome, regulating energy balance and adiposity of their host. We formerly identified that a novel strain of C. minuta (strain DSM33407) boosted microbiota diversity and stimulated deconjugation of the primary bile acid taurocholic acid in human samples. However, there is no description of a bile salt hydrolase (BSH) protein carried in the genome of C. minuta. Here, we identified and cloned a protein from C. minuta’s genome that carries a potent BSH activity, which preferentially deconjugates glycine-conjugated bile acids. We then retrieved 14,319 putative BSH sequences from the NCBI database and filtered them using the UHGP database to collect a total of 6701 sequences that were used to build the most comprehensive phylogenetic tree of BSH-related enzymes identified in the human microbiome so far. This phylogenetic tree revealed that C. minuta’s BSH amino acid sequence clusters away from others with a threshold of 70% identity. This is therefore the first description of C. minuta’s BSH protein, which may be involved in its unique role within the human gut microbial ecosystem.